Advanced assembly language - Holzner, Steven; Peter Norton Computing Corporation (New York Brady, 1991)
A utility for writing working assembly language programs using assembler software. The text provides a functional approach covering keyboard, screen handling, and file handling among other topics. The disk contains over one hundred ready-to-run programs. Assumes the user has some assembly language background.
Title from t.p. of book.
Not copy-protected.
Intermediate or advanced assembly language programmers.
System requirements: IBM PC, PS/2, or compatibles; 640K; DOS 2.0 or higher; Microsoft Macro assembler (version 5.1) or Borland's TASM program; monochrome or color monitor; 2 disk drives; printer (optional).
Keywords: Programming languages (Electronic computers) -- Software; Utilities (Computer programs) -- Software